A Statistical Randomness Generation Algorithm Based on Nonlinear Behavior of Discrete Time Chaotic Systems - Tanyıldızı, Erkan; Özkaynak, Fatih (My University, 2020)
Statistical randomness is a critical requirement for many applications. Generally, it is common to use a generator algorithm for statistical randomness. In this study, a generator algorithm proposed benefiting from chaotic systems. This proposed approach is based on chaotic maps with a simpler mathematical model compared to other chaotic system classes. So the generator has high practical applicability. In addition, optimization algorithms to guarantee statistical properties of generator.
Keywords: Optimization; chaos; Randomness